The NORMA software tool for ORM 2 - Curland, Matthew; Halpin, Terry (Springer Berlin Heidelberg, 2011)
Second generation Object-Role Modeling (ORM 2) is a prime exemplar of fact-orientation, an approach that models the underlying facts of interest in an attribute-free way, using natural sentences to identify objects and the roles they play in relationships. ORM 2 provides languages and procedures for modeling and querying information systems at a conceptual level as well as mapping procedures for transforming between ORM structures and other structures, such as Entity Relationship (ER) models, class models in the Unified Modeling Language (UML), relational database models, extensible markup language schemas (XSD), and datalog. This paper provides an overview of Natural ORM Architect (NORMA), an ORM 2 tool under development that is implemented as a plug-in to Microsoft Visual Studio. For data modeling purposes, ORM typically provides greater expressive power and semantic stability than provided by UML or industrial versions of ER. NORMA’s support for automated verbalization and sample populations facilitates validation with subject matter experts, and its live error-checking provides efficient feedback to modelers.